The Impact of service quality on University services Demand: Applied research at private Dijlah University (Journal of Accounting and Financial Studies ( JAFS ), 2019)
One of the most important problems that would continuously face the Higher  education  organizations is how to  improve the service level  presented by them, and how this can lead to increase demand for services of this organizations.As this issue has exhausted many organizations pushed some of them to withdraw from the market Because of weaknesses in their services. Here lies the importance of this matter to be given more attention in order to maintain the organization competitive position. According to that, The selection of the research title (The Impact of Quality on the Level of the University Service Request) which seeks to measure the impact of service quality on the level of demand, At a time when  world  is moving to rely on the services in supporting their economy and To achieve the goal of this research model supposedly built for research included the independent variable and the dependent variable,And sub-variants, and formulated two main hypotheses,To test the hypotheses random sample was selected to represent the research community,Where the sample included 100 people, representing a slice of the students from first stage, second, third and fourth in Dijlah University College in Baghdad,Gathering information about the research sample was by using questionnaire, And data has been processed by using a set of descriptive and quantitative statistical methods To study the relationship and the impact between the research variables and dimensions.